Antibacterial effect of nanometer‐size grafted layer of quaternary ammonium polymer on poly(ether ether ketone) substrate. Issue 37 (7th February 2020) - Oai, Keiko; Inoue, Yuuki; Nakao, Aiko; Fukazawa, Kyoko; Ishihara, Kazuhiko
Abstract: Owing to its excellent physicochemical properties, poly(ether ether ketone) (PEEK) has been used clinically for medical implants. However, its surface properties should be improved to further enhance its compatibility with a living organism and infection resistance. Here, we examined the surface construction via a combined process, that is, the self‐initiated photoinduced graft polymerization of N, N ‐dimethylaminoethyl methacrylate (DMA) on PEEK substrate followed by polymer quaternization using various bromoalkanes (Q‐PDMA‐ g ‐PEEK). Using a Fourier transform infrared spectroscopy and X‐ray photoelectron spectroscopy, the grafting and quaternarization of poly(DMA) (PDMA) on the PEEK substrate was confirmed. The degree of quaternizations was at least 60% even when the various bromoalkanes were reacted. The Q‐PDMA‐ g ‐PEEK with 1‐bromooctane (BrC8 ) (C8 ‐Q‐PDMA‐ g ‐PEEK) substrate exhibited the highest ζ‐potential of other Q‐PDMA‐ g ‐PEEK substrates. However, no significant differences were observed in the degree of quaternization, thickness of the polymer layer, and hydrophilicity of all modified PEEK substrates. In addition, from antibacterial test with Escherichia coli, the C8 Q‐PDMA‐ g ‐PEEK substrate exhibited the highest antibacterial rate (80%) among Q‐PDMA‐ g ‐PEEK substrates examined. Therefore, we concluded that the surface ζ‐potential is the one an important parameter for manufacturing PEEK substrates with bactericidal properties. Abstract :